Regioselective hydroxylation of steroid hormones by human cytochromes P450. (May 2015) - Niwa, Toshiro; Murayama, Norie; Imagawa, Yurie; Yamazaki, Hiroshi
Abstract This article reviews in vitro metabolic activities [including Michaelis constants (Km), maximal velocities (Vmax) and Vmax/Km] and drug–steroid interactions [such as induction and cooperativity (activation)] of cytochromes P450 (P450 or CYP) in human tissues, including liver and adrenal gland, for 14 kinds of endogenous steroid compounds, including allopregnanolone, cholesterol, cortisol, cortisone, dehydroepiandrosterone, estradiol, estrone, pregnenolone, progesterone, testosterone and bile acids (cholic acid). First, we considered the drug-metabolizing P450s. 6β-Hydroxylation of many steroids, including cortisol, cortisone, progesterone and testosterone, was catalyzed primarily by CYP3A4. CYP1A2 and CYP3A4, respectively, are likely the major hepatic enzymes responsible for 2-/4-hydroxylation and 16α-hydroxylation of estradiol and estrone, steroids that can contribute to breast cancer risk. In contrast, CYP1A1 and CYP1B1 predominantly metabolized estrone and estradiol to 2- and 4-catechol estrogens, which are endogenous ultimate carcinogens if formed in the breast. Some metabolic activities of CYP3A4, including dehydroepiandrosterone 7β-/16α-hydroxylation, estrone 2-hydroxylation and testosterone 6β-hydroxylation, were higher than those for polymorphically expressed CYP3A5. Next, we considered typical steroidogenic P450s. CYP17A1, CYP19A1 and CYP27A1 catalyzed steroid synthesis, including hydroxylation at 17α, 19 and 27 positions, respectively. However, it was difficult to predict which hepatic drug-metabolizing P450 or steroidogenic P450 will be mainly responsible for metabolizing each steroid hormone in vivo based on these results. Further research is required on the metabolism of steroid hormones by various P450s and on prediction of their relative contributions to in vivo metabolism. The findings collected here provide fundamental and useful information on the metabolism of steroid compounds.